Bomb‐14C Peak in the North Pacific Recorded in Long‐Lived Bivalve Shells (Mercenaria stimpsoni). Issue 4 (25th April 2018) - Kubota, Kaoru; Shirai, Kotaro; Murakami‐Sugihara, Naoko; Seike, Koji; Minami, Masayo; Nakamura, Toshio; Tanabe, Kazushige
Abstract: The excess radiocarbon produced by nuclear bomb testing in the atmosphere in the 1950s–1960s (bomb‐ 14 C) is used as a tracer in the surface ocean, extending our understanding of geophysics and biogeochemical cycles. However, there is no bomb‐ 14 C record for the high‐latitude western North Pacific Ocean because of the paucity of long‐lived marine calcifying organisms equivalent to reef‐building corals. The shells of Stimpson's hard clam, Mercenaria stimpsoni, potentially provide such a record because the clam's lifespan is very long (>100 years). We analyzed 14 C in six live‐caught M. stimpsoni shells from the western North Pacific (39.4°N, 142°E) and report, for the first time, the bomb‐ 14 C record with robust calendar ages based on annual growth increments. The value was constant in 1934–1952 (Δ 14 C = −66‰), with a sudden increase in 1959, a peak in 1974 (107‰), which was 60‰ lower than that of the Kuroshio Current, a gradual decline after 1974, and a current value of 16–18‰, which is ∼10‰ higher than the atmospheric value. The bomb‐ 14 C values are between the Kuroshio Current (the northwestern subtropical gyre) and Oyashio Current (the Western Subarctic Gyre) values, suggesting that the Tsugaru Current, downstream from the Kuroshio Current, mixes with the Oyashio Current after passing through Tsugaru Strait. Key Points: First bomb‐ 14 C peak reconstruction in the high‐latitude NW Pacific made with a high‐resolution analysis of long‐lived bivalve shells Relatively high bomb‐ 14 C peak, though at high latitude (40°N), is due to water transport by Kuroshio Current Bomb‐ 14 C record provides a reliable tracer of water mixing